Hidradenitis Suppurativa as a Paradoxical Side Effect to the Use of Adalimumab in Patients with Crohn’s Disease? - Beraldo RF (Clinical and Experimental Gastroenterology, 2020)
Rodrigo Fedatto Beraldo,1 Mariana Barros Marcondes,1 Julio Pinheiro Baima,1 Jaqueline Ribeiro Barros,1 Madhoor Ramdeen,2 Rogerio Saad-Hossne,3 Ligia Yukie Sassaki1 1Department of Internal Medicine, São Paulo State University (Unesp), Medical School, Botucatu, Brazil; 2Inflammatory Bowel Disease Unit, Saint Mark’s Hospital, London, UK; 3Department of Surgery, São Paulo State University (Unesp), Medical School, Botucatu, BrazilCorrespondence: Ligia Yukie Sassaki Email ligiasassaki@gmail.comBackground: Hidradenitis suppurativa is a chronic inflammatory skin disorder associated with inflammatory bowel disease. However, it can arise as a paradoxical side effect of anti-TNF treatment.Methods: The article reports on three patients with Crohn’s disease who developed hidradenitis suppurativa during the treatment with adalimumab.Results: Case 1: A 38-year-old female exhibited an infiltrative lesion in the inguinal region and vulva, consistent with hidradenitis suppurativa, after three months of adalimumab. These lesions were treated with partial vulvectomy. Case 2: After adalimumab treatment, a 27-year-old female, originally diagnosed with ileocolonic Crohn’s disease, went into clinical and endoscopic remission. The patient eventually presented two hyperchromic nodules in the inguinal region, which were diagnosed as hidradenitis suppurativa. The patient showed improvement after treatment with oral doxycycline and local therapy. Case 3: A 34-year-old female with fistulizing and stenosing ileocolonic Crohn’s disease, started adalimumab in 2010, with optimization in 2015. One year after, the patient developed bilateral, erythematous, hardened, inguinal nodulations with purulent drainage, consistent with hidradenitis suppurativa. Treatment with oral doxycycline, fusidic acid, and infiltration with triamcinolone resulted in partial improvement of the lesions. In 2018, the lesions deteriorate. The patient underwent surgical treatment.Conclusion: Patients with inflammatory bowel disease are more likely to the development of other mediated inflammatory diseases, such as hidradenitis suppurativa. Hidradenitis suppurativa may appear as a paradoxical reaction to anti-TNF therapy. Clinical teams must be aware of this type of complication. Early diagnosis and treatment are essential for controlling the disease and preventing the onset of complications.Keywords: hidradenitis suppurativa, Crohn’s disease, adalimumab, inflammatory bowel disease